PRAKTEK PEMBUATAN JALAN HUTAN DAN PERMASALAHANNYA DI DAERAH PROPINSI JAMBI - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1991)
An obseroation on road  construction practice and its problems in two logging company areas in Jambi Province was conducted in  1990. The spcific playeical condition of  the area observed is quite light  and,  therefore, the coat of road construction is low at Rp 5.84 million/km main road grading.Road  densities  are  5. 3 m/ha in the first   and 11.2 m/ha in the second company area. For these roads. land area used amounts to  111.2'4 ha from the total of  19,940 ha logged-over. area or  0.56% in the first and  401.70 ha from the area of  35,021 ha logged-over  area or  1.15%  in  the second company. The ratio of road length to log volume extracted are 0.21 m/cu.m in the  first  and 6.69 m/cu.m  in the second  company.The rate of natural vegetation growth along  forest roads is quite high which is very helpful in retarding soil  erosion potential of the roads.